The advent of ECMO and pumpless extracorporeal lung assist in ARDS - Hamid, I A (Medknow Publications, 2011)
Despite advances in critical care facilities and ventilation therapies acute respiratory distress syndrome (ARDS) is associated with high mortality rates. The condition can stem from a multitude of causes including pneumonia, septicemia and trauma ultimately resulting in ARDS. ARDS is characterized by respiratory insufficiency with severe hypoxemia or hypercapnia. The treatment strategy depends on the knowledge of the underlying disease. But lung-protective ventilation with adjusted positive end-expiratory pressure remains the most effective therapeutic tool despite advances in prone positioning, inhalation of nitric oxide and the use of steroids. Newer modalities including extracorporeal membrane oxygenation (ECMO) and pumpless extracorporeal lung assist (PECLA) are being increasingly introduced in critical care settings as rescue therapies in patients who fail to respond to conservative measures. We describe here the introduction and advances of both ECMO and PECLA in the management of ARDS.